Perbedaan Kecemasan dan Koping Mahasiswa Program A dan Program B dalam Penyelesaian Skripsi: Differences in Anxiety and Coping of Program A and Program B Students in Thesis Completion - Esi Afriyanti; Dira Chika Vidrianta; Elvi Oktarina (Fakultas Keperawatan Universitas Andalas, 2024)
In completing their theses, students from Program A and Program B often face various obstacles that can lead to anxiety. One approach to managing this anxiety is through coping strategies, which vary among students depending on their individual anxiety levels. This study aimed to determine the differences in coping strategies based on anxiety levels between students in Program A and Program B during their thesis completion. The research utilized a comparative, cross-sectional study design. The population consisted of 99 students from the nursing faculty across both programs. Data were collected using the Taylor Manifest Anxiety Scale (TMAS) and a coping strategies questionnaire. The analysis was conducted using frequency distribution, chi-square, and Mann-Whitney tests, with a significance level of p < 0.05 and a 95% confidence interval. The results showed that both Program A and Program B students experienced moderate anxiety, with 69.4% and 59.5%, respectively. Students in Program A predominantly used emotion-focused coping (53.2%), while students in Program B primarily employed problem-focused coping (81.1%). The chi-square test revealed no significant relationship between anxiety levels and coping strategies in Program A (p-value 0.459), whereas a significant relationship was found in Program B (p-value 0.001). Additionally, there was a significant difference in coping strategies and anxiety levels between students in both programs (p < 0.05). Based on these findings, it is recommended that students utilize effective coping strategies problem focused coping to manage anxiety, thereby facilitating timely thesis completion.